38th parallel: The confrontation between the DPRK and the Republic of Korea - Umurbaev Rustam Shakirjanovich (Zien Journals, 2023)
The Korean Peninsula was at one point in history a single unified entity until World War II happened. The Northern half was under occupation by the communist USSR, and the Southern half was occupied by the US. The occupation and the subsequent Korean War ensured that the two nations would take diverging paths that have set them apart to this day
Keywords: Economy; productive; eventually; complicated